2021
DOI: 10.1080/2162402x.2020.1866287
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell transcriptome analysis of CAR T-cell products reveals subpopulations, stimulation, and exhaustion signatures

Abstract: Chimeric antigen receptor (CAR) T-cell adoptive therapy is set to transform the treatment of a rapidly expanding range of malignancies. Although the activation process of normal T cells is well characterized, comparatively little is known about the activation of cells via the CAR. Here we have used flow cytometry together with single-cell transcriptome profiling to characterize the starting material (peripheral blood mononuclear cells) and CAR therapeutic products of 3 healthy donors in the presence and absenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 30 publications
2
18
0
Order By: Relevance
“…These findings suggest that under the given experimental conditions exposure of T cells to LV particles results in stronger gene expression profile alterations than presence of the CAR. While CD8+ CAR high cells exhibited an activated TH1 phenotype and an overall profile well in accordance with that observed in previous studies ( Figure 4 ), 16 , 17 , 20 CD8 CAR neg/low cells expressed genes that potentially restricted cell viability, phenotype, and viral entry. These cells had upregulated genes involved in inhibition of T cell activation ( PIK3IP1 ) and proliferation ( CD37, BTG1 ) as well as promoting pyroptosis ( CASP5 ), a type of programmed cell death resulting in inflammatory cytokine release ( Figures 4 A, 4D, and 4H).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These findings suggest that under the given experimental conditions exposure of T cells to LV particles results in stronger gene expression profile alterations than presence of the CAR. While CD8+ CAR high cells exhibited an activated TH1 phenotype and an overall profile well in accordance with that observed in previous studies ( Figure 4 ), 16 , 17 , 20 CD8 CAR neg/low cells expressed genes that potentially restricted cell viability, phenotype, and viral entry. These cells had upregulated genes involved in inhibition of T cell activation ( PIK3IP1 ) and proliferation ( CD37, BTG1 ) as well as promoting pyroptosis ( CASP5 ), a type of programmed cell death resulting in inflammatory cytokine release ( Figures 4 A, 4D, and 4H).…”
Section: Discussionsupporting
confidence: 90%
“…Notably, previous studies have not described this. 16 , 17 , 18 , 19 , 20 Since the expression profiles of CAR low and CAR neg cells were basically identical, they were merged for the downstream analyses ( Figure S2 A). The situation appears more complicated with the CD8A low population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the advent of revolutionized single-cell mRNA sequencing (scRNA-seq), it is now possible to characterize the full spectrum of immune cell functional states and gene programs in a comprehensive and unbiased manner. Although not fully used, several reports have leveraged scRNA-seq to compare the transcriptional states of 4-1BB and CD28 CAR T cells, 11 to understand the clonal kinetics and transcriptional programs preinfusion and postinfusion, 12 to identify pre-existing CD19-negative subclones, 13 to reveal subpopulations, stimulation, and exhaustion signatures, 14 and to track dynamic development of CAR T cell dysfunction in clinical samples. 15 Yet despite some transcriptomic features have been identified associated with the clinical observations, 16 17 how the constitutional properties of these cellular products mediate therapeutic activities is incompletely understood.…”
Section: Introductionmentioning
confidence: 99%
“…They have also found an enrichment of central memory cell phenotype and fatty acid metabolism in CD8 + 4-1BB CAR-T cells. In another large-scale single-cell transcriptomic analysis of third-generation CAR-T cells that target both B cell maturation antigen (BCMA) and transmembrane activator, calcium modulator, and cyclophilin ligand interactor (TACI), Wang et al have found that CAR products from three different donors exhibit a similar cellular composition, the manufacturing process of CAR-T cells induces effector-like transcriptional signatures, and the CAR-specific antigen exposure activates similar pathways as those triggered by TCR [37] .…”
Section: Delineating the Mechanisms Underlying Immunotherapiesmentioning
confidence: 99%